Stochastic stability of discrete-time Markovian jump antilinear systems - Qian, Y.; Wu, A.; Liu, Wan-Quan (IEEE Computer Society, 2014)
In this paper, we investigate the discrete-time antilinear systems with Markovian jumping parameters. The concept of stochastic stability is extended to the context of discrete-time Markovian jump (DTMJ) antilinear systems. By using stochastic Lyapunov approaches, necessary and sufficient conditions are established for a DTMJ antilinear system to be stochastically stable in terms of coupled anti-Lyapunov matrix equations.